1998
DOI: 10.1172/jci480
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin AT1 receptor blockade abolishes the reflex sympatho-excitatory response to adenosine.

Abstract: We tested the hypothesis that endogenous angiotensin II participates in the direct and reflex effects of adenosine on the sympathetic nervous system. Nine healthy men were studied after 1 wk of the angiotensin II type I receptor antagonist losartan (100 mg daily) or placebo, according to a double-blind randomized crossover design. Bilateral forearm blood flows, NE appearance rates, and total body NE spillover were determined before and during graded brachial arterial infusion of adenosine (0.5, 1.5, 5, and 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 50 publications
3
45
0
Order By: Relevance
“…22,23 In volunteers, even the inhibition of endogenous ANG by the AT 1 receptor antagonist losartan attenuated the sympatho-excitatory reflex elicited by adenosine without involving any changes in blood pressure. 24 Such sympathetic activation independent of the baroreceptor reflex may include influences of ANG on peripheral ganglionic transmission. The potential of such actions has been demonstrated with regard to the positive inotropic and chronotropic cardiac responses to ANG that were provoked by local applications to the stellate or caudal cervical ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In volunteers, even the inhibition of endogenous ANG by the AT 1 receptor antagonist losartan attenuated the sympatho-excitatory reflex elicited by adenosine without involving any changes in blood pressure. 24 Such sympathetic activation independent of the baroreceptor reflex may include influences of ANG on peripheral ganglionic transmission. The potential of such actions has been demonstrated with regard to the positive inotropic and chronotropic cardiac responses to ANG that were provoked by local applications to the stellate or caudal cervical ganglia.…”
Section: Discussionmentioning
confidence: 99%
“…Several neural mechanisms, arising from skeletal muscle, have the capacity to increase the set point for central sympathetic outflow in HF at rest or during exercise. These include: 1) a sympathoexcitatory reflex, stimulated by adenosine, with the participation of angiotensin acting via the AT 1 receptor as a neural intermediary (88,89); 2) increases in local venous pressure (90); 3) activation, in HF, of a muscle mechanoreflex (91) elicited by passive exercise; and 4) a muscle metaboreflex elicited by both isotonic and isometric handgrip (6,89). The latter is activated at a lower workload in HF than in age-matched healthy control subjects, and intensifies in those in whom predicted exercise VO 2 peak falls below 56% (6).…”
Section: Afferent Mechanismsmentioning
confidence: 99%
“…7,8 We previously suggested that endogenous adenosine contributes to the activation of muscle afferents involved in the exercise pressor reflex in humans, 9 in part based on the observation that intra-arterially administered adenosine produces reflex sympathetic activation by stimulating forearm afferents. 6 Some investigators have provided independent confirmation of these findings, 10,11 but others have expressed concern that the sympathetic activation may be explained by a spillover of adenosine into the systemic circulation with the activation of peripheral arterial chemoreceptors. 12,13 Controversy also has arisen about the ability of adenosine to activate myocardial afferents.…”
mentioning
confidence: 99%